MONITORING OF THE INFLUENCE OF HYPODYNAMIC FACTORS AND PHYSICAL PREPARATION OF STUDENTS - Mekhmonov, Ravshan (Журнал иностранных языков и лингвистики, 2022)
The article describes the results of sociological research conducted on the relations of physical education and sports activities with the students of different departments of the university in addition to the faculty of physical culture, and the current issues of organizing activities for the purpose of forming the physical culture of a healthy lifestyle in students.